Current Situation and Countermeasures of Teaching Chinese Guqin - Zhao, Jiejing; Li, Yan (International Journal of Global Economics and Management, 2024)
The guqin, as one of the traditional Chinese musical instruments, carries rich cultural connotation and historical value. However, in modern society, guqin teaching is facing a series of challenges, such as uneven distribution of teaching resources, teaching methods that do not match with modern educational needs, and lack of systematic teaching materials. By analyzing the current situation of guqin teaching, this article explores the reform and countermeasures of guqin teaching, with a view to providing reference for the future development of guqin education. The article firstly gives a brief introduction to the historical background and cultural connotation of the guqin, and then analyzes the traditional and modern teaching modes of the guqin. Through comparative analysis, the article points out the existing problems of guqin teaching, and puts forward a series of reforms and countermeasures against these problems, including innovative teaching modes, optimizing curricula and teaching materials, and strengthening the construction of teachers. Finally, the article emphasizes the importance of promoting guqin culture and puts forward suggestions such as organizing various types of guqin concerts and promoting guqin knowledge popularization activities.